Association Between Employment Status and Objectively Measured Physical Activity and Sedentary Behavior: The Maastricht Study - Pulakka Anna; Stenholm Sari; Bosma Hans; Schaper Nicolaas C; Salverberg Hans HCM; Stehouwer Coen DA; van der Kallen Carla JH; Dagnelie Pieter C; Sep Simone JS; Koster Annemarie (Williams & Wilkins, 2022)
Objective: To examine the association between employment status and physical activity and sedentary
behavior.Methods:We included 2045 participants from The Maastricht Study, who used a thigh-worn
accelerometer. We compared time spent sedentary, standing, stepping and higher intensity physical
activity between participants with different employment status (non-employed or low-, intermediate- or
high-level occupation) with ANOVA.
Results: Participantsinlow-level occupationswere less sedentary
and standing and stepping morethan those in other occupational categoriesand nonemployedparticipants.
Among the employed, the differenceswere mostly observed on weekdays,
whereas the differences in sedentary time and standing between those in low-level occupations and
non-employed participants were evident both on weekdays and weekend days.Conclusions:Those in
low-level occupational category were less sedentary and more active than non-employed and those in
other occupational categories, especially on weekdays.